2012
DOI: 10.1007/s12012-012-9174-y
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-induced Copper Loss and Suppression of Angiogenesis in the Pathogenesis of Myocardial Infarction

Abstract: Myocardial ischemia is a primary cause for the loss of vital components such as cardiomyocytes in the heart, leading to myocardial infarction and eventual cardiac dysfunction or heart failure. Suppressed angiogenesis plays a determinant role in the pathogenesis of myocardial infarction. In response to myocardial ischemia, hypoxia-inducible factor-1α and 2α (HIF-1α and HIF-2α) accumulate in cardiomyocytes and other cell types. This would up-regulate the expression of genes involved in angiogenesis such as vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…Kok et al (1988) show that the adjusted risk of death from cardiovascular disease was about four times higher for subjects in the highest serum Cu quintile compared with those with normal levels, indicating that high serum Cu is associated with the mortality of cardiovascular disease. Although there is not necessarily a direct causeeffect relationship between the development of MI and Cu concentration, it is frequently assumed that Cu is MI risk factor (Gomez et al, 2000;He & James Kang, 2013). Researchers have found that high dietary Cu increased all lipid classes and fatty acid unsaturation (palmitoleic, oleic, linoleic acids), decreased stearic acid in phosphatidylcholine and phosphatidylethanolamine of heart (Jenkins & Kramer, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Kok et al (1988) show that the adjusted risk of death from cardiovascular disease was about four times higher for subjects in the highest serum Cu quintile compared with those with normal levels, indicating that high serum Cu is associated with the mortality of cardiovascular disease. Although there is not necessarily a direct causeeffect relationship between the development of MI and Cu concentration, it is frequently assumed that Cu is MI risk factor (Gomez et al, 2000;He & James Kang, 2013). Researchers have found that high dietary Cu increased all lipid classes and fatty acid unsaturation (palmitoleic, oleic, linoleic acids), decreased stearic acid in phosphatidylcholine and phosphatidylethanolamine of heart (Jenkins & Kramer, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements are being increasingly recognized as essential mediators of the development and progression of MI [3,4]. Although there is no necessarily a direct cause-effect relationship between the development of MI and trace elements status, it is generally believed that the disturbances of them, such as zinc (Zn) and copper (Cu), are risk factors for MI [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is distinct from vasculogenesis, and is responsible for majority of blood vessel growth during development and in pathological conditions. 39,40 A hypoxia-inducible program, driven by HIF-1α, renders endothelial cells responsive to angiogenic signals. 41,42 Normally, when sufficient oxygen is available, HIF-1α may be hydroxylated by the oxygen-sensing enzymes named proteins PHD1-3.…”
Section: Discussionmentioning
confidence: 99%